Transformasi Cerita Pendek Dogdog Pangrewong Menjadi Komik Digital - Haris Santosa Nugraha; Agus Suherman; ANNISA AZIZAH (Universitas Muria Kudus, 2026)
This study aims to describe the transformation of the short story Dogdog Pangréwong into a digital comic through an intertextual approach. The research employs a qualitative descriptive method, using the short story Dogdog Pangréwong as the source text and the digital comic created by the researcher as the transformed text. Data were collected through documentation and library research, while the analysis was conducted through close reading, classification of transformation elements, and examination of the intertextual relationship between the two texts. The findings indicate that the transformation from a verbal narrative to a visual-verbal medium involves the preservation of the core narrative structure, adjustments in presentation to accommodate the characteristics of the new medium, and a shift in the system of signs. Despite medium-specific modifications, the original meaning of the story is maintained through selective adaptation. The transformation demonstrates that digital comics function not only as a medium of interpretation but also as a form of revitalization of classical Sundanese literature within the context of digital literacy. Thus, literary adaptation across media does not merely produce a new representational form but also expands the preservation of regional literature. Key words: Dogdog Pangréwong, Digital Comic, Transformation